THE EFFECT OF PROBLEM BASED LEARNING MODEL AND ACHIEVEMENT MOTIVATION ON MATHEMATICS LEARNING OUTCOMES - Lilik Sujiantini Ermawati; Atiqoh; Yoso Wiyarno (Jurnal Mantik, 2022)
The purpose of this research is (1) to find out there are differences in learning outcomes between students using the PBL model and conventional learning, (2) to find out if there are differences in student learning outcomes who have different motivations in students (3) to find out if there are differences in student learning outcomes. the interaction between the Problem Based Learning model and achievement motivation on learning outcomes. This study used a 2X2 factorial quasi-experimental design. Data collection methods commonly used in a study are: tests, interviews, questionnaires, and observations. The data analysis technique in quantitative research uses statistics, in this case the two-way Analysis of Variance (ANOVA) technique. Based on the research, the following results were obtained (1) There are differences in the effect of the Problem Based Learning (PBL) Learning Model with Conventional learning on students' mathematics learning outcomes, (2) There are differences in the mathematics learning outcomes of students who have high achievement motivation and students who have achievement motivation. low. and (3) There is an interaction between the learning model and achievement motivation on mathematics learning outcomes. Learning mathematics by using the Problem Based Learning (PBL) Learning Model, students who have a high level of achievement motivation have better mathematics learning outcomes than students who have a low level of achievement motivation. Based on the results of the study, it was concluded that using the Problem Based Learning (PBL) Learning Model and achievement motivation could improve students' mathematics learning outcomes at SDN Sidomulyo Bangsal Mojokerto. The implication of this research is that the Problem Based Learning (PBL) Learning Model can be used as a way to improve students' mathematics learning outcomes.